Microwave and Enzymatic Extraction of Orange Peel Pectin - Yu, Xian-Chun; Sun, De-Lin (Asian Journal of Chemistry, 2013)
Pollution of inorganic acid can be reduced, pectin yield and purity can be increased by using microwave to process orange peels and then adding complex enzyme to extract pectin. The infrared spectrum showed that orange pectin contained a relatively huge amount of carbohydrates, but no protein. The extract technology was optimized by orthogonal experiments at 250 W microwave power, 50 ºC microwave heating temperature, 10 min microwave processing time, 1 h single extraction time, buffer pH 4.5, 50 ºC enzyme extraction temperature and 0.9 % enzymatic dosage. Enzyme extraction was performed three times. The average yield in orange peel pectin was 22.12 %, which was much higher than the pectin extraction yield using conventional water bath method under the same conditions.